A 20-yr database (1997-2017) of co-seismic displacements from GPS recordings in the Aegean area and their scaling with Mw and hypocentral distance - Ganas, Athanassios; Andritsou, Nikoletta; Kosma, Chrysanthi; Argyrakis, Panagiotis; Tsironi, Varvara; Drakatos, George (Bulletin of the Geological Society of Greece, 2018)
We describe and make available a dataset of 64 data points of Global Positioning System (GPS) displacements for significant, shallow earthquakes in Greece during the period 1997-2017. The displacement data can be used by earthquake geologists, engineers and seismologists in an effort to better understand the faulting process, the rupture mechanics, the pattern of ground-motions, and in engineering applications. We include recordings from GNSS networks at near-source to regional distances (2–132 km) for 11 earthquakes between global CMT moment magnitudes (Mw) 5.5 and 6.9. We also model the magnitude scaling properties of peak ground horizontal displacements (PGD and PGD-S) for these events using L1-norm minimisation regression. Our data indicate an almost linear attenuation of seismic strain with distance for this range of seismic magnitudes. We developed a set of relationships based on PGD (in cm) and distance to hypocentre R (in km), which may be used for the rapid estimation of the earthquake magnitude in near real-time. MwPGD = [LOG(PGD) + 8.2849]/(1.6810 – 0.2453LOGR) MwPGD-S = [LOG(PGD-S) + 8.0839]/(1.6793 – 0.2447LOGR)